A Pathway Analysis of Hereditary Hemochromatosis-related Genes and Pancreatic Ductal Adenocarcinoma Risk (FS11-05-19). (13th June 2019) - Julián-Serrano, Sachelly; Yu, Kai; Yuan, Fangcheng; Wheeler, William; Karimi, Parisa; Amundadottir, Laufey; Jacobs, Eric; Kraft, Peter; Li, Donghui; Petersen, Gloria M; Risch, Harvey A; Wolphin, Brian; et al.
Abstract: Objectives: Hereditary primary hemochromatosis is characterized by dysregulation of iron homeostasis and is caused by a genetic predisposition to absorb too much iron from foods. Hemochromatosis has been associated with some chronic diseases, including hepatocellular carcinoma and type 2 diabetes mellitus. Type 2 diabetes is an established risk factor and high red meat intake has been associated with pancreatic ductal adenocarcinoma (PDAC). We hypothesize that genetic susceptibility to hemochromatosis as determined by known hereditary hemochromatosis-related genes will be associated with PDAC. Methods: We conducted a pathway analysis of genes known to contribute to hereditary hemochromatosis using the summary-based adaptive rank truncated product (sARTP) method on GWAS summary statistics derived from 9038 PDAC cases and 12, 389 controls of European descent collected by the Pancreatic Cancer Cohort Consortium (PanScan) and the Pancreatic Cancer Case-Control Consortium (PANC4).Our analysis included 7 hereditary hemochromatosis genes ( HFE, BMP2, HJV, HAMP, TFR2, SLC40A1, and FTH1 ) and close genomic regions (20 kb upstream and 20 kb downstream) with a total of 176 single nucleotide polymorphisms (SNPs). The sARTP method combines SNP-level associations across SNPs in a gene or a pathway. Results: The hereditary hemochromatosis pathway was significantly associated with PDAC ( P -value = 0.011). HJV and TFR2 genes contributed the most to the association with PDAC risk (gene level P -values = 0.003 and 0.013, respectively). Conclusions: This study supports the hypothesis that genetic susceptibility related to hereditary hemochromatosis genes are associated with PDAC. Further studies should evaluate the modifying effect of iron-rich foods and genetic susceptibility of hemochromatosis and PDAC risk. Funding Sources: This work was supported by the Intramural Research Program, Division of Cancer Epidemiology and Genetics, National Cancer Institute, National Institutes of Health.